2000
DOI: 10.1152/ajpregu.2000.278.6.r1424
|View full text |Cite
|
Sign up to set email alerts
|

Energy intake-independent modulation of triglyceride metabolism by glucocorticoids in the rat

Abstract: This study aimed to dissociate the peripheral effects of adrenalectomy (ADX) on triglyceride (TG) metabolism from those it exerts centrally on energy intake and to determine the impact of diet composition therein. Rats were fed either rodent chow or a diet high in sucrose and fat (HSF) and were adrenalectomized or left intact and pair fed to the ADX animals. Liver TG content, an index of hepatic TG production, was not affected by ADX, but was increased twofold by the HSF diet. ADX decreased the rate of hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
6
1
Order By: Relevance
“…Similar results were observed in another study using adrenalectomized rats with diet-induced obesity demonstrating the effects of GC action on plasma and liver triglyceride levels, plasma insulin, and adipose tissue weight [85]. These effects appear to be minimized when there is restriction on high-energy diet [86], suggesting they may be exerted via mediating the central ingestive behavior. These findings highlight the central role of GCs in the development of obesity and other features of the Metabolic Syndrome.…”
Section: The Metabolic Effects Of Gcssupporting
confidence: 80%
“…Similar results were observed in another study using adrenalectomized rats with diet-induced obesity demonstrating the effects of GC action on plasma and liver triglyceride levels, plasma insulin, and adipose tissue weight [85]. These effects appear to be minimized when there is restriction on high-energy diet [86], suggesting they may be exerted via mediating the central ingestive behavior. These findings highlight the central role of GCs in the development of obesity and other features of the Metabolic Syndrome.…”
Section: The Metabolic Effects Of Gcssupporting
confidence: 80%
“…In particular, reported prolactin effects on liver and white adipose tissue lipogenic gene expression and function are opposite to those observed after ghrelin treatment in the current study (1). In addition, excess glucocorticoids are not reported to exert independent effects on hepatic lipogenesis and lipid deposition (14,29,54), whereas most (16,18,30), although not all (55), reports agree on their suppressive or null effect on skeletal muscle mitochondrial function. Thus, taken together, the above observations do not support a major role of additional hypophyseal hormonal changes in observed metabolic effects.…”
Section: Discussioncontrasting
confidence: 65%
“…Other studies have reported comparable results in rodents fed ad libitum with a similar diet [3], but apparently never within a pair-fed model. In fact, a pair-feeding model of HFS diet was performed in Sprague-Dawley rats, although no changes in body weight gain were observed [17]. The strongest evidence of the experimental hypothesis comes from rodent studies in which a high-fat (HF) diet induced obesity independently of total energy intake [18,19].…”
Section: Discussionmentioning
confidence: 99%